Unraveling Religious Symbolism in Tokwi Lasem Batik Motifs: Charles Sanders Peirce's Semiotic Analysis of the Representation of Meaning and Cultural Identity - Doddy Iskandar Cakranegara; Asep Saeful Muhtadi; Abdul Syukur; Dody S. Truna (International Journal of Nusantara Islam, 2026)
This study investigates the representation of religious symbols embedded within the Tokwi Lasem batik motifs, utilizing the semiotic framework of Charles Sanders Peirce. Originating from the Chinese Peranakan community in Lasem, Central Java, these batik motifs carry profound spiritual significance, particularly symbols rooted in Taoist belief systems, such as the Three Star Gods (Fu Lu Shou), the Eight Immortals (Ba Xian), dragons, phoenixes, and Mandarin characters. Employing a qualitative method, data were collected through participatory observation, in-depth interviews with artisans, cultural experts, and curators, as well as a literature review. The findings demonstrate that the motifs serve not merely as decorative art but as sacred signs functioning within Peirce’s triadic model of semiosis—comprising representamen, object, and interpretant. These signs embody a dynamic interplay of religious meaning and cultural memory, forming a visual language that bridges the sacred and the everyday. The motifs reflect a deep-seated syncretism between Chinese Taoist cosmology and Javanese local traditions, articulating identity, reverence, and continuity of belief. Theoretically, this study contributes to the growing body of scholarship on religious semiotics and material culture, while also emphasizing the interpretive richness of traditional batik as a medium of spiritual communication. Practically, the research advocates for the recognition of batik as a living heritage, fostering cultural resilience, interethnic understanding, and localized approaches to heritage education and preservation.